2013
DOI: 10.1002/jor.22484
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic differentiation capacity of subacromial bursal tissue—derived stem cells

Abstract: In this study, analysis and comprehensive comparison of neurogenic differentiation capacity of human bursal tissuederived-stem cells (hBT-SCs) was aimed with human bone marrow derived mesenchymal stem cells (hBM-MSCs). hBT-SCs was isolated from subacromial bursa tissue (n ¼ 3) by collagen type-II digestion. The expression of stem cell markers, differentiation capacity and telomerase activity were determined for both cell lines. The expression levels of neurogenic cell markers were compared consecutively. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…2 ). Interestingly, BS cells have also been shown to be able to undergo neurogenic [ 54 ] and tendogenic differentiation [ 55 ] underlining their potential impact for the treatment of subacromial pathology. Because of the similarities between both cell types, as shown in this work, it is also conceivable that BMSCs, which can be easily obtained from bone marrow, might be harnessed to augment reconstitution of the subacromial bursa after surgical removal, providing potential support for the restoration of the gliding mechanism after such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Interestingly, BS cells have also been shown to be able to undergo neurogenic [ 54 ] and tendogenic differentiation [ 55 ] underlining their potential impact for the treatment of subacromial pathology. Because of the similarities between both cell types, as shown in this work, it is also conceivable that BMSCs, which can be easily obtained from bone marrow, might be harnessed to augment reconstitution of the subacromial bursa after surgical removal, providing potential support for the restoration of the gliding mechanism after such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although donor variability could not be excluded in previous work, such types of analyses revealed that alkaline phosphatase and cluster of differentiation 34 and 106 expression could further distinguish between BCs and BMCs, and that certain aspects such neurogenic, gland, and vascular development were more present in BCs on array screening for whole genome expression. 9 This is supported by the work of Aydın and coworkers, 10 who found higher levels of neurotrophic factors in BCs compared with BMCs, which might be harnessed for any approach toward restoration of the neuromuscular unit and the neurogenic control of cell turnover of the soft tissues in the subacromial space.…”
Section: See Related Article On Page 2978mentioning
confidence: 80%
“…3g ). As an effective survival factor, CNTF can reduce tissue destruction during inflammation and protect damaged neurons from degeneration and necrosis [ 66 ]. This explains why the density of myelinated nerve fibers in intermittent dASCs and sustaining dASCs 7d groups were significantly greater than those in the hollow and uASCs groups at both the early stage (6 weeks after cell transplantation) and late stage (12 weeks after cell transplantation), but especially at the early stage (Fig.…”
Section: Discussionmentioning
confidence: 99%